GLAPD: Whole Genome Based LAMP Primer Design for a Set of Target Genomes - Jia, Ben; Li, Xueling; Liu, Wei; Lu, Changde; Lu, Xiaoting; Ma, Liangxiao; Li, Yuan-Yuan; Wei, Chaochun (Frontiers in Microbiology, 2019)
Loop-mediated isothermal amplification(LAMP) technology has been applied in a wide range of 16 fields such as detection of foodborne bacteria and clinical pathogens due to its simplicity and 17 efficiency. However, existing LAMP primer designing systems require a conserved gene or a short 18 genome region as input, and they can’t design group-specific primers. With the growing number of 19 whole genomes available, it is possible to design better primers to target a set of genomes with high 20 specificity based on whole genomes. We present here a whole Genome based LAMP Primer 21 Designer (GLAPD), a new system to design LAMP primer for a set of target genomes using whole 22 genomes. Candidate single primer regions are identified genome wide and then combined into LAMP 23 primer sets. For a given set of target genomes, only primer sets amplifying them and only these 24 genomes will be output. In order to accelerate the primer designing, a GPU version is provided as 25 well. The effectiveness of primers designed by GLAPD has been assessed for a wide range of 26 foodborne bacteria. GLAPD can be accessed at http://cgm.sjtu.edu.cn/GLAPD/ or 27 https://github.com/jiqingxiaoxi/GLAPD.git.